N. F. S. Grundtvig: "Indfald". Af Grundtvigarkivets fasc. 327, udgivet med kommentarer - Toldberg, Helge (Grundtvig-studier, 1949)
Grundtvig: “ Aphorisms” (edited by Helge Toldberg). 1. When there is no need to close a book, but only to turn over its pages, in order to find something of interest, the reader has no cause for complaint. 2. It is the real quill-drivers who talk like books. 3. A slave ran away from his master, became a citizen of Rome among thieves and robbers, was made Emperor and put upon his master all the fetters which both he and his fellow-citizens had deserved — that in brief is the history of the pen which ran away from the spoken word. 4. The Germans both write and quote far more books than we do, and I have often wondered how they could, but now I have discovered that they can very well do so, for they read correspondingly fewer. 5. Antiquity saw beyond itself and therefore said more of what it saw than of what it did; the mediaeval period was confined within itself and therefore its ideas were only of medium size, but it put all that it said into practice; the modern period sees beyond them both, but winks at itself; therefore it prates about the loftiest things and does the lowest, daily promises more and fulfills less. 6. The thought of eternity only delighted the people of ancient times, therefore they clutched at it everywhere; it only terrified those of the Middle Ages, therefore they either fled from it or were slaves to it; it both humbles and comforts the people of modern times, and thefore naturally it alternately attracts and repels us. 7. The spirit of mankind is the Phoenix which soared singing towards the rising sun in ancient times, dissolved and sank into ashes under the midday sun in the Middle Ages, and in modern times came out of the egg as a little worm (the book-worm), but will presently take on the shape and wings and voice of a bird again to sing evensong as the sun goes down. 8. The expanse of heaven represents the universality of ancient times, and the sea that of the mediaeval period, so there seems to be no natural image left for the modern period except the yawning, empty, bottomless abyss; but if it, like the mediaeval period, will allow itself to be enclosed by ancient times, it will yet discover in the expanse of heaven far brighter prospects — the lights of heaven, which are to be seen everywhere. 9. Every language which one learns to speak from books is a mulatto or half-breed begotten by a black, and by a dead one into the bargain, so it is a ghost, which only as a changeling gets into the cradle af the natural child stolen away by the goblins. — Applied to the speaking of Latin, especially classical Latin, whereby the “black” becomes father, as it were, to Merlin, this gives a horrible result, as history unfortunately shows. 10. One never lacks reasons for what one wants to do. 11. It is the same with self-will as with self-wisdom; the whole is very bad, but we must have the half in order to accomplish anything effectually. If, on the contrary, we obstinately insist upon the whole, the same thing will happen to us as happens to children and mad people, who, where wise folk rule, are wholly denied their will, because they are wholly lacking in wisdom. 12. All wit either bites or strikes, and the real, genuine kind, the flashing wit, strikes down like a thunderbolt, so it always shows sharpness and sometimes power, but never anything else, and it is like dogs and mercenary soldiers who can easily serve two masters, though not at the same time. 13. However, it is only the ordinary taunting, teasing, sarcastic, biting, more or less malicious wit that is like loose dogs and mercenary soldiers, whom one may indeed sometimes be obliged to keep because of thieves and scoundrels, but who must be very well trained if they are not to become a nuisance. The flashing wit which strikes to the root of things does indeed share the sharpness of the others, but neither their venom nor their instability, for it is only the sharpest possible expression of a truth, by which untruth can never be served and which at bottom is always allied with love, though it may easily have appearances against it, just as one may easily be tempted to say of the thunderbolt that it is as terrifying for men as for goblins. 14. Thor in his chariot is the flashing wit, and therefore the only one respected by Loke, who is the sparkling wit. 15. If we want to be truly liberal, we must before all else grant the King his freedom, for it betrays a fundamentally slavish mentality to want to be ruled by a slave. 16. It is completely topsy-turvy to want to have what is new in the Church and what is old in the School, for a faith which was true a thousand years ago is still true, but what was, comparatively speaking, very clever three hundred years ago is very foolish now. 17. With regard to the State we may say that one can live excellently in good old houses with new equipment, but new houses with old-fashioned equipment are intolerable. 18. Light is good, but life is far better still; for even without light life is beyond price, but light without life is not worth a pipe of tobacco. 19. A society may be very pleasant because it is not noisy, but when a great society is absolutely quiet we rightly think and call it dead; so the civic society will never live to experience its golden jubilee, which will only come to pass at its funeral. 20. Our academic instruction with the corresponding examinations is the same kind of trick in the spiritual sphere as it would be in the physical sphere to stuff ourselves up with fruit-stones in order to see how much we could vomit up at a time, and the Latin exercise is like an excrement from something which is fundamentally indigestible, but in which the chemist can discover with pleasure how far such a material can, at the expense af life, be dissolved in the human body. A Gert Westphaler *) who would constantly repeat this pretty story to the philologists would be worth [his weight in] gold. 21. “ Live is learn”, says the proverb; but a wit rightly reversed it, too, and said, “ Learn is live”, for life, after all, is both the first and the last, both the means and the end. 22. People taught children to think instead of giving them something worth while to think about; and in consequence they either flung away their thoughts upon the dunghill, where far more weeds than corn spring up after them, or they built castles in the air until they became homeless upon earth. 23. We would prefer to live with the old man and die with the new; but since that cannot be done, we must much rather live with the new man and die with the old. 24. Nothing for nothing is everywhere like wheaten bread for two farthings, therefore one must never give even only half a farthing for nothing. The above translated aphorisms of N. F. S. Grundtvig, first published in this volume, originate from fasc. 327 of the Grundtvig-Archives at the Royal Library of Copenhagen. During his visits to England G. carried fasc. 327 (a bound book in folio) with him for extracts from books, e. g. several of Shakespeare’s histories and tragedies. The last pages were filled in after his final return in 1831; and on the last four pages we find the aphorisms. Though not quite unique (a smaller collection is to be found in fasc. 305), they are of particular interest as the first rough sketches of ideas elaborated in G.’s famous “ Mythology” (1832). But the importance of Grundtvigian aphorisms is more than casual; F. L. Grundtvig, his youngest son, born in his old age, witnesses that his father was an ardent student of dictionaries, and often framed supplementary annotations or even aphorisms when studying them. The aphorisms crystallize some of Grundtvig’s main ideas in preparing his “ Mythology” and “ World History”, and in one case, at least, anticipate changes in Gr.’s application of symbols. The chief instance is the Phoenix in aphorism 7, where the patristic conception has given way to the one in Lactantius and the Exeter Book; in his poetry this does not take place till 1836. What gives the aphorisms their charm is their gospel of life, as is seen from number 19, the idea of which is that a golden jubilee of the living society could be but its funeral.he deepest impression of G.’s universe is to be found in aphorism 8, the idea of reflexion from heaven to earth as underlying our visual impressions. Antiquity recognized heaven in the sky, and the Middle Ages in the sea, whereas G .’s own age does not worry though only the “ Yawning Abyss” (Ginnungagap) of Old Norse mythology is left for them.